Programmable materials based on periodic cellular solids. Part II: Numerical analysis. (1st December 2016) - Restrepo, David; Mankame, Nilesh D.; Zavattieri, Pablo D.
Highlights: Programmable cellular materials (PCMs) were presented in Part 1. PCMs are robust to rate effects and boundary conditions. PCMs are also robust to defects derived from fabrication and handling. Large PCM samples can be programmed. Effect of contributing factors in PCMs depends on the topology and prog. imperfection. Abstract: A detailed numerical investigation of the programmable materials presented in part I is conducted in this study. The influence of defects and exogenous factors on the programmability of samples from two different programmable cellular material systems is investigated through finite element simulations. The defects studied here are representative of those present in the samples that were tested in the companion paper. These include non-uniform cell wall thicknesses, missing cell walls, misaligned cell walls and fillets at the cell wall junctions. Exogenous factors such as the sample size, friction at the sample boundaries and the strain rate sensitivity of the base material are also included in this study. We base our studies on the analysis of the change of the effective initial modulus on each programmed configuration of both material systems due to these factors. The investigation demonstrates that even in the presence of defects and exogenous factors, programming remains a robust way of modifying the effective initial modulus of programmable cellular materials over a wide range without requiring reprocessing of the material. However, the programmability and the susceptibility to various contributing factors vary with the base material, type of programmed imperfection and the nature of the original cellular solid. Graphical abstract: